Homicidal/violent thoughts, suicidal ideation and violent behavior in adolescents with social phobia in Metropolitan Lima, Perú. (28th April 2014) - Vivar, Roxana; Morón, Giannina; Padilla, Martín; Alarcón, Renato D.
Abstract Introduction Social phobia and violent behavior are both important mental health problems among adolescent populations in different parts of the world. This study attempts to evaluate possible connections between social phobia, homicidal/violent thoughts, suicidal ideation, and subsequent violent behavior among adolescents living in the metropolitan area of Lima, Perú. Methods A sample of 991 adolescents, part of the 2002 Epidemiological Study in Metropolitan Lima, conducted by the National Institute of Mental Health "Honorio Delgado‐Hideyo Noguchi" (INSM "HD‐HN") was studied. Social phobia was diagnosed on the basis of clinical assessment and the use of MINI, and suicidal ideation, homicidal/violent thoughts, and violent behavior were identified through the Mental Health Questionnaire. Odds ratio (OR) statistical analyses adjusted by logistic regression controlling for age and gender were performed. Results Variables associated with social phobia were homicidal thoughts in the last month (OR: 5.19, confidence interval [CI] at 95% 4.95–5.40), an impulse to hit known (OR: 1.56; 95% CI, 1.53–1.59) and unknown (OR: 3.98, 95% CI, 3.89–4.07) persons, the wish to take revenge for a past offense (OR: 2.60, 95% CI 2.54–2.64), getting involved in fights with different kinds of weapons (OR: 1, 78, 95% CI 1.70–1.87), suicidal ideation throughout lifetime (OR: 4.74, 95% CI 4.65–4.83), and life prevalence of suicidal attempt (OR: 5.39, 95% CI 5.23–5.55). Discussion Social phobia in adolescents of this Peruvian sample seems to be closely associated with both homicidal/violent thoughts, violent behavior, and suicidal ideation.